Management Research Based on the Paradigm of the Design Sciences: The Quest for Field‐Tested and Grounded Technological Rules - Aken, Joan E. van (Journal of Management Studies, 2004)
ABSTRACT Academic management research has a serious utilization problem. In this field mainstream research tends to be description‐driven, based on the paradigm of the ‘explanatory sciences’, like physics and sociology, and resulting in what may be called Organization Theory. This article argues that the relevance problem can be mitigated if such research were to be complemented with prescription‐driven research, based on the paradigm of the ‘design sciences’, like Medicine and Engineering, and resulting in what may be called Management Theory. The typical research products in Management Theory would be ‘field‐tested and grounded technological rules’. The nature of such rules is discussed as well as the research strategies producing them.